2013
DOI: 10.1109/jdt.2012.2227682
|View full text |Cite
|
Sign up to set email alerts
|

Semipolar $({\hbox{20}}\bar{{\hbox{2}}}\bar{{\hbox{1}}})$ InGaN/GaN Light-Emitting Diodes for High-Efficiency Solid-State Lighting

Abstract: This work examines the effects of polarization-related electric fields on the energy band diagrams, wavelength shift, wave function overlap, and efficiency droop for InGaN quantum wells on various crystal orientations, including polar (0001) ( -plane), semipolar 2021 , semipolar 2021 , and nonpolar 1010 ( -plane). Based on simulations, we show that the semipolar 2021 orientation exhibits excellent potential for the development of high-efficiency, low-droop light-emitting diodes (LEDs). We then present recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 323 publications
(165 citation statements)
references
References 45 publications
3
162
0
Order By: Relevance
“…45,46 Generally, the much smaller droop of nonpolar and semipolar LEDs in comparison with polar LEDs has been attributed to the weaker polarization fields. [30][31][32][33]47,48 However, it should be noted that low-efficiency polar LEDs also show a relatively small droop, 35,36 which has been attributed mainly to the strong effect of non-radiative recombination processes. Recently, Davies et al 49 have suggested that the droop is inherent to the carrier density in InGaN QW structures and independent of crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Generally, the much smaller droop of nonpolar and semipolar LEDs in comparison with polar LEDs has been attributed to the weaker polarization fields. [30][31][32][33]47,48 However, it should be noted that low-efficiency polar LEDs also show a relatively small droop, 35,36 which has been attributed mainly to the strong effect of non-radiative recombination processes. Recently, Davies et al 49 have suggested that the droop is inherent to the carrier density in InGaN QW structures and independent of crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The development of InGaN/GaN quantum well (QW) based violet-blue-green light-emitting diodes (LEDs) [1][2][3][4][5][6] and laser diodes (LDs) [7][8][9][10] enables efficient solid-state lighting (SSL) technology for a wider range of applications, such as general illumination, automotive lighting, display and horticulture [11,12]. Besides, the utilization of III-nitride LEDs and LDs as the transmitter for free-space visible light communications (VLC) and underwater wireless optical communications (UWOC) has been demonstrated and investigated recently [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the design and performance of the demonstrated GaN-based SLDs, comparing the emission wavelength, substrate material, configuration, waveguide design, and the maximum light output power reported in each case. 405 nm c-GaN "j-shape" waveguide curved ridge 350 mW (cw) [24] 408 nm c-GaN "j-shape" waveguide "j-shape" ridge 200 mW (cw) [25] 410 ~ 445 nm c-GaN tilted waveguide 2 µm ridge 30 ~ 55 mW (cw) [26] 420 nm c-GaN tilted facet 2 µm ridge 2 mW (cw) 100 mW (pulse) [27] 420 nm c-GaN "j-shape" waveguide AR/HR coating 3 µm ridge 200 mW (cw) [28] 439 nm m-GaN facet roughening 4 µm ridge 5 mW (pulse) [29] 443 nm c-GaN curved waveguide 2 µm ridge 100 mW (cw) [30] 445 nm c-GaN oblique facet 5 µm ridge - [31] 447 nm Semipolar GaN passive absorber 7.5 µm ridge 256 mW (cw) [17] 500 nm c-GaN curved waveguide 2 µm ridge 4 mW (pulse) [32] Since most of InGaN/GaN QW SLDs are grown on a polar, c-plane GaN substrate, there is a growing interest to develop high efficient violet-blue SLDs on nonpolar or semipolar substrates owing to a reduced polarization field presented in the QW structure [2]. Studies on semipolar and nonpolar GaN-based LEDs and LDs have revealed that the enhanced electron and hole wavefunction overlap is expected for InGaN/GaN QWs grown on nonpolar (m-plane) and semipolar GaN substrates, leading to an enhanced internal quantum efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the micro LED design needs more improvement for practical solid-state lighting due to its low power and potentially issues with pixel-control. Furthermore, LEDs suffer a loss in external quantum efficiency (EQE) as operating current increases, commonly known as "efficiency droop" [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%